Professional baseball athletic trainers' perceptions of preparation for job-specific duties - Gardiner-Shires, A.; Marley, S. C.; Barnes, J. C.; Shires, M. E. (Journal of Athletic Training, 2012)
Context: The extent to which individuals are prepared completely for work in a particular athletic training setting (eg, professional sports, college, high school) is unknown. This issue is critical today, and findings in this area have implications for athletic training education policy and employers. Objective: To determine the perceptions of preparation for work-specific tasks by professional baseball athletic trainers (PBATs). We also wanted to determine whether various preparation experiences interact with perceived skills. Design: Cross-sectional study. Setting: Online survey administered via Survey-Monkey. Patients or Other Participants: Two hundred seventy-five PBATs. Intervention(s): The PBATs reported their levels of preparation before employment in their positions and their current skills in each of the 8 work task domains: evaluation of elbow injuries; evaluation of shoulder injuries; evaluation of general injuries; acute care; injury prevention; treatment, rehabilitation, and reconditioning; organization and administration; and non-athletic-training tasks. Main Outcome Measure(s): Nine repeated-measures analyses of covariance were performed with each perception of preparation (retrospective, current) as a within-subject factor. Preparation experiences were included as between-subjects factors, and number of years working in baseball was the covariate. Results: Subscale reliabilities were calculated and found to be between 0.79 and 0.97. A total of 180 PBATs (65%) completed the survey. The backgrounds and routes by which PBATs gained employment in the professional baseball setting varied. Individuals who completed professional baseball internships, had previous work experience, and immediately entered the professional baseball setting after graduation had noted differences in their perceptions of preparation for work tasks. The PBATs indicated they were substantially underprepared for tasks in the organization and administration and non-athletic-training task domains. Conclusions: The organizational socialization process is complex, and no 1 experience appears to completely prepare an individual for work in the professional baseball setting.